2014
DOI: 10.1186/s12916-014-0188-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of multimorbidity in China and implications for the healthcare system: cross-sectional survey among 162,464 community household residents in southern China

Abstract: BackgroundChina, like other countries, is facing a growing burden of chronic disease but the prevalence of multimorbidity and implications for the healthcare system have been little researched. We examined the epidemiology of multimorbidity in southern China in a large representative sample. The effects of multimorbidity and other factors on usual source of healthcare were also examined.MethodsWe conducted a large cross-sectional survey among approximately 5% (N = 162,464) of the resident population in three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
150
9
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(191 citation statements)
references
References 36 publications
24
150
9
8
Order By: Relevance
“…Current evidence posits that having a usual source of care will translate into a trustful and satisfactory relationships between PLCDs and their providers [35]. A recent community-based study conducted in a southern region in China demonstrated that patients with chronic conditions tended to use secondary care instead of primary care as their regular source of care [36]. Our findings are consistent with this line of evidence.…”
Section: Discussionsupporting
confidence: 88%
“…Current evidence posits that having a usual source of care will translate into a trustful and satisfactory relationships between PLCDs and their providers [35]. A recent community-based study conducted in a southern region in China demonstrated that patients with chronic conditions tended to use secondary care instead of primary care as their regular source of care [36]. Our findings are consistent with this line of evidence.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, multimorbidity was identified in one-third of the participants of our study. Other investigations reported that education was inversely associated with multimorbidity, while aging was directly related [23,24,25,26,27,28]. However, a little more than one-third of participants with multimorbidities from our study were young and middle-aged adults.…”
Section: Discussioncontrasting
confidence: 64%
“…Characteristics associated with gender, age, level of education, employment status, and marital status were examined in recent PHC studies [23,24,25,26,27,28,51]. Consideration of these aspects might be especially relevant in low- and middle-income countries (LMICs), where socioeconomic and cultural inequities may predispose the conditions for the establishment of several risk factors associated with chronic diseases and multimorbidity [51,53,54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Featured research topics in Figure 5 were based on the top cited publications from each income group in each year: high–income countries [2,13,2336], upper–middle income countries [8,37–45], lower-middle income countries [7,9,4650], and low–income countries [5153]. …”
Section: Resultsmentioning
confidence: 99%